Concurrent Phenologies of Three Semiaquatic Bugs (Heteroptera: Gerridae, Veliidae) on a Small River in Central Illinois, USA - Steven J. Taylor (Psyche: A Journal of Entomology)
The phenology of three species of Gerroidea (Heteroptera), Metrobates hesperius Uhler (Gerridae), Rhagovelia oriander Parshley (Veliidae), and Rhematobates tenuipes Meinert (Gerridae), was studied on a river in central Illinois (USA). Metrobates hesperius was the most abundant species, and was active from mid-May through mid-October. It was bivoltine and overwintered as eggs. Matinig and oviposition of M. hesperius were observed in mid-July. Rhagovelia oriander was present from mid-May to mid-November. This species was bivoltine (or possibly trivoltine), overwintering as eggs. Rheumatobates tenuipes was not active until early August, and was present to mid-November and was univoltine. It overwinters as adults and possibly as nymphs, and may undergo an extended early season diapause. The three species occupied differing microhabitats and differed in periods of peak abundance, with M. hesperius being most abundant from mid-May through the first of August, and R. tenuipes being most abundant from early August to mid-November.